Stem Cell Therapy for Hashimoto's Disease - a Promising Treatment Method? - Oliwia Kozyra; Katarzyna Paluch; Zofia Szypuła; Mateusz Koper; Klaudia Ratyna; Adrian Konaszczuk; Jessica Kałuża; Aleksandra Nowak; Oliwia Bochenek; Małgorzata Skarbek (Nicolaus Copernicus University in Toruń, 2024)
Hashimoto's disease, an autoimmune disorder characterized by chronic inflammation and progressive destruction of the thyroid gland, leads to hypothyroidism and a range of metabolic disturbances. Conventional treatments primarily focus on hormone replacement therapy, which does not address the underlying autoimmune mechanisms. Stem cell therapy has emerged as a potential revolutionary treatment for Hashimoto's disease, aiming to regenerate thyroid tissue and modulate the immune response. This abstract explores the potential of stem cell therapy in restoring thyroid function and reducing autoimmune activity. Preclinical studies using animal models and in vitro human cell studies have demonstrated promising results, showing that stem cells can reduce thyroid inflammation, promote tissue regeneration, and restore hormone production. Early-phase clinical trials are underway to assess the safety and efficacy of mesenchymal stem cells (MSCs) and other stem cell types in patients with Hashimoto's disease. Despite the promise, challenges such as immune rejection, ethical considerations, regulatory hurdles, and cost must be addressed. Ongoing research and technological advancements hold the potential to transform the treatment landscape for Hashimoto's disease, offering hope for improved outcomes and quality of life for patients.